Modern America and the Legacy of Founding - Pestritto, Ronald J.; West, Thomas G. (Lexington Books, 2006)
This is the third and final volume in the series on American political thought edited by Ronald J. Pestritto and Thomas G. West. The book addresses how the major themes in American political thought_identified in the first two books of the series_have played out in the world of modern American politics. The first volume focused on the founding era, and examined the prevalence of social-compact theory among the founders and implications of that theory for the design of American institutions. The second volume examined the major challenges that nineteenth-century thought posed to the political ideas of the founding, and suggested that these challenges created tensions that would significantly affect the development of American politics in the twentieth century and beyond. In Modern America and the Legacy of the Founding, the authors address these fundamental tensions: how does modern America resolve the inherent conflict between the original constitutional order and the challenges posed by modern liberalism? The authors look at the contemporary effects of this fundamental tension on questions of foreign policy and domestic policy, and on questions of our national political institutions and the ideas that shape them today.